Faktor Faktor Yang Mempengaruhi Status Gizi pada Balita Literature Review - I Wayan Angga Radiastu; Jasrin H Tombora (Jurnal Ventilator, 2024)
The nutritional status of toddlers is an important thing that every parent must know. Malnutrition during this golden age is irreversible (cannot be recovered). Malnutrition can affect a child's brain development. Malnutrition among children under five in Indonesia appears to be increasing from year to year. Malnutrition can occur due to internal and external factors that are not prevented or addressed as early as possible and have an impact on health conditions, growth and development of toddlers, and productivity in adulthood. This phenomenon reveals the importance of preventive efforts to prevent the risk of malnutrition in children under five from all possible risk factors. This article aims to review and analyze factors that influence the nutritional status of toddlers through the literature review method. There are 5 main articles used and have been selected through search results on the Google Scholar database. The results of the study found that factors that influence nutritional status in toddler include infectious diseases, knowledge, birth spacing, socio-economics, parenting patterns.